The Effect of Prenatal Yoga on Sleep Quality of Pregnant Women in The Third Trimester At PMB Restu Bunda - Wati, Rosma; Kusumastuti, Kusumastuti; Sofiana, Juni; Tyas, Sindy Febrianing (Placentum: Jurnal Ilmiah Kesehatan dan Aplikasinya, 2025)
Background:  Sleep quality often declines during the third trimester of pregnancy due to significant physiological and psychological changes, such as frequent urination, back pain, anxiety, and emotional fluctuations. These disturbances can negatively impact maternal health and fetal development.Objective:This study aimed to examine the effect of gentle prenatal yoga on sleep quality among third-trimester pregnant women at PMB Restu Bunda, Kebumen.Methods:A quasi-experimental design with a one-group pretest–posttest approach was used. The study involved 40 pregnant women in their third trimester selected by total sampling. Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI) before and after five sessions of gentle prenatal yoga conducted over two weeks. Each session lasted 30–60 minutes and included diaphragmatic breathing, gentle stretching, and relaxation poses (cat– cow, butterfly, mountain, and side-lying savasana), led by a certified prenatal yoga instructor. Data were analyzed using the Wilcoxon signed-rank test with a significance level of p < 0.05.Results:Before the intervention, 85% of participants had poor sleep quality. After participating in prenatal yoga, 92.5% reported good sleep quality. The Wilcoxon test showed a significant improvement in sleep quality (Z = -5.868, p = 0.001).Conclusion:Gentle prenatal yoga significantly improves sleep quality in third-trimester pregnant women. It can be recommended as a safe and effective complementary therapy in antenatal care to promote maternal relaxation and healthy pregnancy outcomes.